Reference simulations of noncanonical nucleic acids with different χ variants of the AMBER force field: quadruplex DNA, quadruplex RNA and Z-DNA - Krepl, Miroslav; Zgarbová, Marie; Stadlbauer, Petr; Otyepka, Michal; Banáš, Pavel; Koča, Jaroslav; Cheatham, Thomas E; Jurečka, Petr; Sponer, Jiří (Journal of chemical theory and computation, 2012)
Refinement of empirical force fields for nucleic acids requires their extensive testing using as wide range of systems as possible. However, finding unambiguous reference data is not easy. In this paper, we analyze four systems which we suggest should be included in standard portfolio of molecules to test nucleic acids force fields, namely, parallel and antiparallel stranded DNA guanine quadruplex stems, RNA quadruplex stem, and Z-DNA. We highlight parameters that should be monitored to assess the force field performance. The work is primarily based on 8.4 μs of 100-250 ns trajectories analyzed in detail followed by 9.6 μs of additional selected back up trajectories that were monitored to verify that the results of the initial analyses are correct. Four versions of the Cornell et al. AMBER force field are tested, including an entirely new parmχ(OL4) variant with χ dihedral specifically reparametrized for DNA molecules containing syn nucleotides. We test also different water models and ion conditions. While improvement for DNA quadruplexes is visible, the force fields still do not fully represent the intricate Z-DNA backbone conformation.